full solution of this question.
fast
Attachments:
![](https://hi-static.z-dn.net/files/db2/465bff10ad6b029a8e7fd59696af52c1.jpg)
Answers
Answered by
1
Step-by-step explanation:
(a + b + c)³ - a³ - b³ - c³
⇒ (a + b)³ + c³ + 3(a + b)²c + 3(a + b)c² - a³ - b³ - c³
⇒ a³ + b³ + 3a²b + 3ab² + c³ + 3(a + b)²c + 3(a + b)c² - a³ - b³ - c³
⇒ a³ + b³ + 3ab(a + b) +c³ + 3(a + b)c [a + b + c] - a³ - b³ - c³
⇒ 3ab(a + b) + 3(a + b)c[a + b + c]
⇒ 3(a + b)[ab + ca + cb + c²]
⇒ 3(a + b)[a(b + c) + c(b + c)]
⇒ 3(a + b)(b + c)(c + a)
Hope it helps. If helped, mark as brainliest!
Similar questions
Math,
6 months ago
English,
6 months ago
Economy,
1 year ago
Science,
1 year ago
Social Sciences,
1 year ago